Disproval of the Starch-Amyloplast Hypothesis? - Richter, Peter; Strauch, Sebastian; Lebert, Michael (Trends in Plant Science, 2019)
In a recent publication, Edelmann (Protoplasma 2018; 255,1877-1881) refuted the well-established starch-amyloplast hypothesis of gravitropism in plants. Gravitropic curvatures of shoots and roots were still present after amyloplast- containing tissues (in sheath of vascular bundles and root caps) were dissected. Here, we discuss Edelmann's data in the light of Popper's falsification principle.
CRIS-Team WoS Importer:2019-04-02